2014
DOI: 10.1152/physrev.00039.2013
|View full text |Cite
|
Sign up to set email alerts
|

Selenoproteins: Molecular Pathways and Physiological Roles

Abstract: Selenium is an essential micronutrient with important functions in human health and relevance to several pathophysiological conditions. The biological effects of selenium are largely mediated by selenium-containing proteins (selenoproteins) that are present in all three domains of life. Although selenoproteins represent diverse molecular pathways and biological functions, all these proteins contain at least one selenocysteine (Sec), a seleniumcontaining amino acid, and most serve oxidoreductase functions. Sec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
896
2
27

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(934 citation statements)
references
References 386 publications
(459 reference statements)
9
896
2
27
Order By: Relevance
“…However, the function of SelK during ERAD remains unclear. According to recent studies, SelS and SelK have been shown to associate with each other through their transmembrane domains, although the association might also involve additional proteins (24,43). In this study, p97(VCP) was required for the interaction of SelS with SelK (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…However, the function of SelK during ERAD remains unclear. According to recent studies, SelS and SelK have been shown to associate with each other through their transmembrane domains, although the association might also involve additional proteins (24,43). In this study, p97(VCP) was required for the interaction of SelS with SelK (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…A high activity of these enzymes has been demonstrated in the thyroid tissue; however, in order to maintain iodine metabolism, catalysed by deiodinases, and at an appropriate level, low activity of these enzymes will be enough, much lower than of other selenoproteins in the pathways of the metabolic turnover of proteins, fats, and amino acids [34,77,78]. Therefore, neither the concentration of selenium nor the concentrations of selenium-containing proteins directly influence the selenium content in the thyroid and the activity of selenoproteins contained in the TG [69,79].…”
Section: Prace Poglądowementioning
confidence: 99%
“…3,4 The functional activity of selenoproteins might be due to their anti-oxidative effects or to an altered expression pattern of genes involved in cancer initiation and progression. 5,6 This was further strengthened by epidemiologic studies revealing an inverse correlation of the Se status and cancer incidence as well as cancer mortality. 7 Furthermore, Se is one of the few trace elements, for which anticarcinogenic effects have been proven in a randomized, double blinded, placebo controlled study.…”
Section: Introductionmentioning
confidence: 93%